The Metabolic Effects of Natural Sugars, Refined Sugars and Low-Calorie Sweeteners - Pepin, Alexandra (Université d'Ottawa / University of Ottawa, 2026)
This thesis evaluated the metabolic effects of natural sugars, refined sugars and low-calorie sweeteners in healthy individuals. Two narrative reviews, one comprehensive critical review and one experimental study were conducted. The first narrative review examined the metabolic health effects associated with the consumption of both sugar-sweetened beverages and natural fruit juices. Specifically, it summarized the physiology of glucose and fructose metabolism and their distinct impacts on metabolic health, with particular emphasis on blood lipid profiles. However, the limited evidence on metabolic effects beyond systemic low-grade inflammation, combined with significant discrepancies in study designs and measured outcomes, prevents the formulation of evidence-based recommendations regarding whether fruit juices represent healthier alternatives to sugar-sweetened beverages. The second article reviewed the potential metabolic health effects associated with low-calorie sweetener consumption, also an alternative to sugar-sweetened beverages. Aimed at informing physicians and clinicians, it provided a concise overview of the available evidence in French, thereby contributing to knowledge dissemination and enhancing scientific accessibility within francophone communities. Since the publication of this narrative review, substantial new evidence has emerged examining the effects of low-calorie sweeteners, particularly sucralose, on glucose homeostasis and gut microbiota. To contextualize and deepen these findings, the third article presents a comprehensive and critical synthesis of current evidence specifically addressing the cumulative effects of sucralose consumption on postprandial glycemic responses in humans. Furthermore, it explores the potential role of gut microbiota composition and functionality in mediating metabolic outcomes. Building on the mechanistic insights and study limitations synthesized in this critical review, the fourth article presents a randomized controlled trial designed under real-world conditions to evaluate the cumulative effects of sucralose consumption on postprandial glycemic responses and related physiological mechanisms in healthy adults (NARELO study). These potential mechanisms included alterations in gut microbiota profiles, intestinal barrier permeability and systemic low-grade inflammation. In this study, we demonstrated that the realistic consumption of sucralose-sweetened beverages for 21 days impairs postprandial glycemic responses in healthy adults compared to sugar-sweetened beverages (P_Bonf = 0.040), in the absence of significant changes in insulin concentrations, body composition, gut microbiota composition, fecal concentrations of SCFAs and BCFAs, and plasmatic biomarkers of intestinal permeability and systemic low-grade inflammation. Clinically, postprandial glycemic responses were 8.4% higher following the three-week consumption of sucralose-sweetened beverages, based on estimated marginal means (baseline: 5.00 mmol/L, 95% CI 4.36–5.64; post-intervention: 5.42 mmol/L, 95% CI 4.78–6.06). Further, we also explored whether free sugars derived from natural sources elicit distinct metabolic responses compared with refined sugars. To this end, 100% natural fruit juice was included as an exploratory comparator. No meaningful differences were observed in glucose tolerance when comparing natural fruit juice to sugar-sweetened beverages. Collectively, the findings of this thesis challenge the prevailing assumption that low-calorie sweeteners are physiologically inert, emphasizing the need for compound-specific evaluation as the food industry advances toward the next generation of sweeteners. Although a definitive mechanistic explanation remains elusive, the work presented herein considerably advances our understanding of the potential long-term effects of low-calorie sweeteners on glucose homeostasis. Overall, this thesis provides critical evidence on the metabolic impacts of natural sugars, refined sugars, and low-calorie sweeteners, offering valuable insights to inform public health guidelines.
Keywords: low-calorie sweeteners; fruit juices; sugar-sweetened beverages; refined sugars; natural sugars; sugar substitutes; artificial sweeteners; sucralose; nonnutritive sweeteners; gut microbiome; gut microbiota; glycemic control; glucose homeostasis; glucose tolerance; systemic low-grade inflammation; intestinal permeability; added sugars; postprandial glycemic responses; orange juice